Returns to Sepharad in the Work of Esther Bendahan. - FLESLER, DANIELA (Revista de Estudios Hispánicos, 2021)
This article explores some of the fictional work of Esther Bendahan, one of the very few Spanish writers of Moroccan Sephardi descent living in Spain today. Her novels, Soñar con Hispania (co-written with Esther Benari, 2002) and Déjalo, ya volveremos (2006), as well as her short story "Condecoración" (2016), explore what it means to "return" to Sepharad in contemporary Spain. Bendahan's writing captures with particular poignancy the difficulty of avoiding well-established clichés when speaking for and about Sephardi Jews in Spain. These time-sanctioned myths still provide the available grammar through which it is possible to speak, and to be listened to, as Sephardi Jews in Spain. This article shows how Bendahan's fictional work explores and negotiates with this available grammar.